Dominance of toxigenic Clostridioides difficile strains and the appearance of the emerging PCR ribotype 955 in hospitals in Silesia, Poland - Szarek, Klaudia; Frankowska, Natalia; Kabała, Monika; Smits, Wiep Klaas; Wultańska, Dorota; Lalowski, Piotr; Pituch, Hanna; Iwanicki, Adam; Hinc, Krzysztof; Harmanus, Céline; Sanders, Ingrid M. J. G.; Wojtyczka, Robert; et al. (Frontiers in Microbiology, 2025)
IntroductionToxigenic strains of Clostridioides difficile are the leading cause of healthcare-associated bacterial infections in Poland. In the Silesian Voivodeship, with 4.5 million inhabitants, the incidence of C. difficile infection (CDI) in 2023 reached 65.1/100,000, slightly down from 70.0/100,000 in 2022. This study aimed to investigate the occurrence of toxigenic C. difficile ribotypes in hospitalized patients in Silesia.Materials and methodsA total of 130 stool samples from patients with confirmed antibiotic-associated diarrhea were tested. Multiplex PCR detected genes for GDH, toxins A/B, binary toxin CDT, and 16S rDNA. Ribotyping was performed by capillary PCR, and antibiotic susceptibility was tested with ETEST for 10 antibiotics.ResultsMultiplex PCR confirmed the presence of all toxins (A+B+CDT+) in 97 isolates. Six strains (6%) represented ribotype 955 (RT955), first reported in Poland in 2023. RT027 remained dominant (60%, n = 78). All isolates were susceptible to vancomycin, while 4% (5/130) showed metronidazole resistance.ConclusionRT027 remains prevalent among CDI cases in Silesia. The emergence of RT955, closely related to a UK epidemic strain, suggests a possible shared origin and epidemiological link.